2011
DOI: 10.1073/pnas.1107762108
|View full text |Cite
|
Sign up to set email alerts
|

Role of structurally and magnetically modified nanoclusters in colossal magnetoresistance

Abstract: It is generally accepted that electronic and magnetic phase separation is the origin of many of exotic properties of strongly correlated electron materials, such as colossal magnetoresistance (CMR), an unusually large variation in the electrical resistivity under applied magnetic field. In the simplest picture, the two competing phases are those associated with the material state on either side of the phase transition. Those phases would be paramagnetic insulator and ferromagnetic metal for the CMR effect in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…The first appearance of magnetic domain wall contrast was observed at T = 118 K. This temperature is about 7 K lower than the Curie temperature of the same TEM sample as measured from magnetometry to be T c = 125 K. This difference can attributed to the fact that at temperatures very close to T c , the ferromagnetic domain signal is too weak to be detected using Lorentz TEM. Similar differences between temperature at which magnetic contrast is observed and the Curie temperature have previously been reported 13,20 . The area fraction of the sample that was ferromagnetic was calculated as a function of temperature from this series of images.…”
Section: B Ferromagnetic Transitionsupporting
confidence: 67%
See 1 more Smart Citation
“…The first appearance of magnetic domain wall contrast was observed at T = 118 K. This temperature is about 7 K lower than the Curie temperature of the same TEM sample as measured from magnetometry to be T c = 125 K. This difference can attributed to the fact that at temperatures very close to T c , the ferromagnetic domain signal is too weak to be detected using Lorentz TEM. Similar differences between temperature at which magnetic contrast is observed and the Curie temperature have previously been reported 13,20 . The area fraction of the sample that was ferromagnetic was calculated as a function of temperature from this series of images.…”
Section: B Ferromagnetic Transitionsupporting
confidence: 67%
“…Only recently there have been some efforts towards direct real space visualization of the way in which the small FM regions form and become connected, leading to the formation of FM domains within the material below T c . Lorentz transmission electron microscopy (LTEM) has also been used to study cubic manganites since it offers high spatial resolution and a direct visualization of the magnetic domains [11][12][13] . Furthermore with current advanced in-situ capabilities, LTEM offers unique possibilities to study the magnetic phase transitions as a function of temperature, while simultaneously obtaining information about structural and charge ordering using electron diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Mn 3+ and Mn 4+ ions together with the site-site double-exchange (DE) mechanism (1) appear to capture the essence of this phenomenon. A plethora of experimental and theoretical investigations have recently suggested that the ground states of manganites are intrinsically inhomogeneous and characterized by the presence of competing phases (2)(3)(4)(5)(6)(7)(8) extending over domains at nanoscale/mesoscale. High pressure (P) has a triggering effect for phase separation because either magnetic or structural domains have been observed in compressed manganites (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The strong coupling between charge, spin, orbital, and lattice degrees of freedom, supplemented by weak disorder, leads to unusual colossal response phenomena in manganites [1][2][3][4] . There has been intense focus over last two decades to validate the phase coexistence/competition scenario [5][6][7][8][9][10][11][12][13][14][15][16][17][18] , which is believed to be a necessary ingredient to explain the resistivity hump in colossal magnetoresistive (CMR) manganites. Furthermore, understanding the phase competition in bulk manganites helps in designing low-dimensional manganite nanostructures with emergent physical phenomena [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%